2015
DOI: 10.1039/c5cp02198g
|View full text |Cite
|
Sign up to set email alerts
|

Cu(i) stabilizing crosslinked polyethyleneimine

Abstract: Polyethyleneimine (PEI) is known for its metal-coordinating properties and in its crosslinked form has applications in different areas ranging from drug delivery to waste water treatment and recovery of trace metals. With the aim to regulate the coordination environment of Cu(I) and Cu(II) ions in marine coatings, we have prepared a triazole cross-linking agent with 'soft' coordination that can crosslink PEI via indirect reductive amination. We have shown that this triazole crosslinker not only increases the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Nitrogen‐rich, cross‐linked polyethylene imine is known for binding metal ions such as copper and rare earth metals due to the metal chelating property . Its particular selectivity for binding copper ions and its absorption kinetics in a variety of media has extensively been studied .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrogen‐rich, cross‐linked polyethylene imine is known for binding metal ions such as copper and rare earth metals due to the metal chelating property . Its particular selectivity for binding copper ions and its absorption kinetics in a variety of media has extensively been studied .…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen-rich, cross-linked polyethylene imine is known for binding metal ions such as copper and rare earth metals due to the metal chelating property. [33,34] Its particular selectivity for binding copper ions and its absorption kinetics in a variety of media has extensively been studied. [24][25][26][27]35,36] Here, cross-linked PEI was loaded with copper ions by immersing the PEI-coated conducting carbon cloth in a known concentration of copper sulfate solution.…”
Section: Wwwadvsustainsyscommentioning
confidence: 99%
“…The noticeably blue and cyan colors of the PEI-functionalized and TerP-functionalized membranes are consistent with changes expected for Cu 2+ binding by these different chemistries. 62,63 The higher affinity and high capacity Cu 2+ binding exhibited by membranes functionalized with tailored chemical moieties suggest that the binding characteristics of these films can be systematically altered or optimized through the appropriate selection of metal binding groups. No significant change in the sorbent capacity was observed upon recycling these membranes through at least 10 adsorption and regeneration cycles (Supporting Information, Figure S14).…”
Section: Resultsmentioning
confidence: 99%
“…and dissociation (Kd) constants (Equation 1.1), but the group acknowledged that the release of Cu(II) may require an artificial intervention, such as an electrochemical stimulus. 77,79 Furthermore, considering that > 99% of the Cu(II) dissolved in seawater is already strongly complexed by unidentified organic ligands with formation constants in the range of 10 9 -10 14 , the ligand in the coating would have to be a stronger Cu(II)-chelator than the natural ligands in seawater (i.e. Kf > 10 14 ).…”
Section: Conceptmentioning
confidence: 99%
“…Although, in the literature, the more popular route seems to be the incorporation of the ligand in the polymeric binder. 41,79,87,110,111 For example, Trojer et al 87 reported methods for affixing pendant azole ligands, which are strong Cu(II)chelators, to polymers for protection against fouling organisms. El-Wahab et al 112 simply add-mixed arylhydrazone ligand o-methoxybenzaldehyde benzoylhydrazone and its metal complexes in a polyurethane coating, and the film containing the Cu(II) complex had antimicrobial activity against Gram-positive and -negative bacteria and fungi.…”
Section: Formulation Of Cu(ii) Ligands In Coatingsmentioning
confidence: 99%